Histological evaluation of the debris removal efficiency of activation of sodium hypochlorite solution at different concentrations - Esin Özlek; Eda Acikgoz; Nesibe Zeyneb Gökkaya; Ahmet Taşan; Fikret Altındağ (BMC, 2023)
Abstract Background This study aims to histologically evaluate the efficiency of debris removal through activation of 2.5% and 5.25% NaOCI using laser, ultrasonic, and intracanal heating methods. Methods Sixty-four maxillary central incisor teeth were randomly divided into two groups according to the irrigation solution (n = 32); 2.5% NaOCI and 5.25% NaOCI. Subsequently, the samples were further divided into four subgroups according to the final irrigation activation technique (n = 8); SubgroupA: Er,Cs:YSGG laser, SubgroupB: Ultrasonic, Subgroup C: Intracanal heating, Subgroup D: no activation. Generalized Linear Models and Bonferroni tests were used for statistical analysis (p < 0.05). Results The effect of NaOCI concentration was statistically significant (p < 0.001). Furthermore, the activation of NaOCI by laser exhibited a statistically significant difference compared to the ultrasonic and intracanal heating methods (p < 0.001). Conclusion The efficiency of root canal cleaning increases with higher NaOCI concentration. Activation of NaOCI also significantly enhances its effectiveness.